Economic heresies : some old-fashioned questions in economic theory - Robinson, Joan. (London : Macmillan, 1971)
In this subdued theoretical attack, the crusty dean of British economics indicts present-generation Keynesians as neo-neo-classicists. Keynes swept away neo-classical attempts to create models with technology, savings, rate of surplus, or rate of exploitation taken as constants with the mechanical equilibrium of the stationary state then determined; yet economists like Friedman are trying to return to an equilibrium notion of money and national product. Robinson further criticizes the failure to gauge the degree to which imperfect competition influences prices and investment, and the belief in a ""natural"" rate of growth. She provides her own growth model, ""not to predict equilibrium but to map out possible disturbances."" She upholds the precepts that investment is made by firms, not households; wages are paid in money, not neo-classical single commodities; and prices aren't determined under perfect competition....(Kirkus Review)
Includes bibliographical references and index.
rpm 05/10/2017; rpm 11/10/2017
Loans
Keywords: Keynesian economics; Economics